HISTOPATHOLOGICAL STRUCTURE OF LUNG WHITE RAT GIVEN MYERMECODIA PENDANS EXTRACT AND INDUCED DOSAGE OF PARACETAMOL - Merdana, I Made; Mahottama, I Gusti Putu Tovan; Berata, I Ketut; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2022)
Myrmecodia pendan is an epiphytic plant that attaches to large trees. Myrmecodia pendans plant contains chemical compounds such as flavonoids and tannins that are known can cure various diseases. The study aimed to determine the effect of giving myrmecodia pendans extract to the histopathological lung in white rats due to the administration of toxic doses of paracetamol. This study used 24 male white rats and divided into 4 treatment groups. The histopatological changes observed were bleeding, inflammation, congestion and necrosis. The results obtained were the administration of toxic doses of paracetamol orally causes bleeding, inflammation, congestion and necrosis in the lungs of white rats. Giving extract of myrmecodia pendans can improve lung tissue due to the administration of toxic doses of paracetamol which experience bleeding, inflammation, congestion and necrosis in the white rats.